Evaluasi Penggunaan Buku Kia Terhadap Pemanfaatan Pertolongan Persalinan oleh Ibu Hamil Trimester Tiga Systematic Literature Review - Dian Kristiningrum; Euis Badriah; Metty Supyanti; Lisa Trina Arlym (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Maternal and Child Health (MCH) book is a media for communication, education, and important information for pregnant women. The optimal use of this book is expected to enhance the utilization of childbirth assistance by health workers. This article aims to evaluate the relationship between the use of the MCH book and the utilization of childbirth assistance by pregnant women in their third trimester. The research method is a systematic literature review by identifying all published literature using relevant keywords. The selected articles are those published in the last 2 years that are full texts, followed by selection based on titles and abstracts, ultimately finding 8 articles that meet the inclusion criteria and have high quality. The research results show a significant relationship between the level of use of the MCH book and the utilization of childbirth assistance. Thus, the proper use of the KIA book contributes to the increased utilization of delivery assistance by healthcare workers.